An Ordered Alite Cement Clinker Phase (Ca3SiO5, aP162) from Flux Synthesis. Issue 22 (18th October 2021) - Utrap, André; Pielmeier, Markus R. P.; Lange, Tobias; Gädt, Torben; Nilges, Tom
Abstract: Calcium silicates are the main components in cement clinkers. Alite, the nesosilicate or island silicate Ca3 SiO5, also named C3 S in cement chemistry notation, represents the main phase in Portland cement clinkers. Due to the metastability of Alite at room temperature, quenching from high temperatures is mandatory for phase preservation and impurities are important structure directing factors. Those two aspects result in a plethora of published polymorphs. Many Alite polymorphs described in the literature are characterized by various degrees of disorder within the Si−O substructure which is a direct consequence of afore mentioned features (i. e. quenching and presence of impurities). Here we report on the CaCl2 ‐flux mediated synthesis and structural characterization of an aP 162 Alite featuring a fully‐ordered [SiO4 ] tetrahedron substructure. The orientation of the [SiO4 ] tetrahedron substructure is discussed based on the Nishi and Takéuchi nomenclature and is equivalent to the Golovastikov model reported in 1975. Rietveld analyses of a synthetic clinker and three commercial CEM I clinker substantiate that the aP 162 model can successfully be applied for clinker phase analysis. Besides the structural characterization, quantum chemical band structure calculations based on Density Functional Theory methods illustrate the expected electrically isolating character of Ca3 SiO5 . Abstract :